Anxiety, Depression, and Body Weight in Children and Adolescents With Migraine - Tarantino, Samuela; Papetti, Laura; Di Stefano, Alessandra; Messina, Valeria; Ursitti, Fabiana; Ferilli, Michela Ada Noris; Sforza, Giorgia; Moavero, Romina; Vigevano, Federico; Gentile, Simonetta; Valeriani, Massimiliano (Frontiers in Psychology, 2020)
Background There is a lack of studies that explore the possible association between body weight, psychological symptoms and migraine severity in pediatric populations. Purpose of the study was to explore: 1) the association between body weight and the frequency of migraine attacks, 2) the possible differences in anxiety and depression symptoms according to the frequency of attacks and body weight, and 3) the possible mediating role of anxiety and/or depression in the association between body weight and frequency of migraine attacks in children. Methods One hundred and eleven children/adolescents with migraine were included (47 boys, 64 girls; mean age 11.7; ± 2.4 years). Patients were classified in: 1) high frequency patients, reporting from weekly to daily episodes, and 2) low frequency patients, with ≤ 3 episodes per month. According to their Body Mass Index Percentiles, patients were divided in “Normal weight” (from ≥ 5 to < 85 percentile), “Overweight” (from ≥ 85 to < 95 percentile) and “Obese” (≥ 95 percentile). Given the low number of obese patients, overweight and obese groups were considered together in the “Overweight” group. Anxiety and depression symptoms were assessed by Self-Administered Psychiatric Scales for Children and Adolescents (SAFA). Results Fifty-four patients were normal in weight (49.6%), while 56 (50.4%) were overweight. The overweight patients showed higher frequency of migraine attacks (64.7%; p < .05). Patients with high frequency of attacks reported higher scores in all SAFA-Anxiety subscales (SAFA-A Tot: F = 15.107; p = .000). Overweight patients showed a significantly higher score in “Separation anxiety” subscale (F = 7.855; p = .006). We found a mediating role between overweight and high frequency for total anxiety (z = 2.11 ± .03; p < .05) and social anxiety (z = 2.04 ± .03; p <.05). Conclusions Our results suggest that, among children suffering from migraine, overweight status is associated with higher frequency of attacks and separation anxiety symptoms. In particular, our study provides the first evidence of the role of anxiety in linking overweight and frequency of migraine attacks in children and adolescents.